Industrial training report: Jabatan Tanah Dan Galian Negeri Perlis (JTGPs) / Nuraida Aqillah Zainal Azman - Zainal Azman, Nuraida Aqillah (Universiti Teknologi MARA, Perlis, 2024)
This report was written as part of the Bachelor of Business Administration (Hons.) Finance programme requirement. At Jabatan Tanah Dan Galian Negeri Perlis (JTGPs). I finished a 6-month internship programme started form 1st September 2023 until 9th February 2024. All of my time at my company is extremely significant since the experiences I get will help me acquire a better job after I graduate. All of the tasks and assignments that I have done will be included in this report. During my internship, I was allocated to the Registration Unit which was really beneficial to me because I was able to obtain new knowledge and improve my abilities in working environment. During my internship, I was able to get general knowledge of every process and procedure in government sector. My responsibilities in the Registration Unit included my involvement in the auction cases that related to the agencies and the customers. The experience that have a dealing with the customers and the client make me more confident in the working environment. This internship has been a new learning experience that have been expose me in the real environment of working and real government network. Top management also exposed me to the professional route by sharing their expertise in the sector. Overall, my internship has been a positive experience because I have a helpful and caring supervisor as well as congenial co-workers.